(untitled) (GYMNASIUM, 2008)
Stress has appeared at the same time with life, being an attribute of the living. Without stress there is no life, no evolution, but exceeding stress can be harmful. This is stress, good and harmful, always present and necessary. The life of modern people has a fast rhythm and takes place in a totally new environment compared to the previous generations. Life in modern cities, which are overcrowded and polluted, the physical and especially the mental strain, life as a continuous competition, all of these make contemporary life more and more different from the life existing only a few generations before. The life of modern people is in a permanent state of stress. Massage in general and especially the method presented in this paper, due to its effect of making the patient aware of his own bodily reactions, can be classified among the efficient methods that can be used to relieve stress as well as to recover the physical and the mental potential of the body after periods of intense activity, thus restoring the functional balance of the body and preventing illnesses.